The effect of the BATHE interview technique on the empowerment of diabetic patients in primary care: A cluster randomised controlled study - AKMAN, MEHMET; APAYDIN KAYA, MEMNUNE ÇİĞDEM (ELSEVIER SCI LTD, 2017)
Aim: To investigate the effect of the BATHE therapeutic interview technique on the empowerment of diabetes mellitus patients in primary care. Method: A cluster randomised controlled study using the BATHE interview technique was conducted on diabetes mellitus patients in primary care. Physicians in the intervention group were trained in the BATHE interview technique and used it with their diabetic patients in addition to the usual care. In the control group physicians delivered only the usual care. A total of 112 diabetes mellitus patients who met the study criteria (57 intervention, 55 control) were included. Three interviews were conducted with the patients in both groups at the beginning, the 3rd and 6th months. The Diabetes Empowerment Scale (DES) was filled up at baseline and in the 6th month. Results: Due to some drop outs, the study finished with 44 patients in the control and 49 in the intervention group. According to an 'Intention to treat analysis' increase in the DES total score for the intervention group was higher than for the control group (Delta = 10.56+8.97; Delta = 5.64+7.36; p < 0.001). Using multiple regression analysis, the BATHE intervention showed a significant predictor of the DES difference (B: 8.861; CI: 6.092-11.629; p < 0.001). Conclusion: The use of the BATHE technique in primary care has a positive effect on the empowerment of diabetes mellitus patients. (C) 2016 Published by Elsevier Ltd on behalf of Primary Care Diabetes Europe.
Keywords: Diabetes mellitus; Empathy; Primary health care; Family practice; Motivational interviewing; Physician-patient relations; Patient-centered care; Empowerment; EDUCATION; MANAGEMENT; PHYSICIAN